HACCP system management and productivity of restaurants in Lima Metropolitana, Peru (LACCEI, 2024)
The Hazard Analysis and Critical Control Points (HACCP) system is a tool used in the food industry and in the catering sector to ensure the safety of processed foods and its implementation brings with it a better use of raw materials. The purpose of this doctoral thesis is to determine the management of the HACCP system and its influence on the increase of productivity in food service establishments in metropolitan Lima in the year 2020. The study uses a quantitative, correlational, descriptive, non-experimental approach. The sample consisted of 28 restaurant workers who are part of the team that designed, implemented and obtained the certification of the HACCP system of their establishment. For the collection of quantitative data, the HACCCP System Management questionnaire was applied. The analysis of the data shows that 100% of the respondents consider that the management of the HACCP system in their establishment is very good (67.9%) or good (32.1%). Regarding the productivity variable, it was observed that 64.3% consider that their establishments have high productivity indexes and the remaining 35.7% very high. The Spearmam bivariate correlation statistical test showed a correlation index of 0.923 (p = 0.000) between the two variables. It is concluded that there is a very high positive correlation between HACCP management and productivity of food service establishments located in Metropolitan Lima in the year 2020.